Molecular Identfication of Bacillus pumilus BY 16S rRNA from Abattoir Wastewater (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
Abattoir is one of the most pronounced but yet ignored sources of highly recalcitrant wastewater that pose many environmental challenges and cause harm to mankind. However, little was reported on the molecular identification of bacterial committee from the abattoir wastewater. This study aimed at isolation and molecular identification of most abundant bacterium species from wastewater of abattoir. Wastewater sample was collected, isolate and identify the most abundant bacterium by gram staining and microscopy. Genomic DNA (gDNA) was extracted from the isolated bacterium and conducted 16S rRNA PCR amplification. Multiple sequence and phylogenetic relationship among other 8 Bacillus species and 1 outgroup were inferred by comparing the sequence data sets from NBCI. The biochemical identification analyses indicated that the bacterium is gram positive with Bacillus shape and cream-yellow colour. 16S rRNA and bioinformatics analyses demonstrated that the most abundant isolated bacterium is Bacillus pumilus with 99% identification. Moreover, the phylogenetic tree analysis discovered that the identified bacterium from this study is more closely related to Bacillus species as they share the same clade. The sequence is partial as compared with the other deposited sequences in the GeneBank. This study provides an insight on the microbial species of Nigeria abattoir wastewater which was identified using molecular approach. As well, gave a clue for potential treatment of the wastewater.